Two‐Step pH‐Modulated Rapid Assembly of Trace‐Element‐Doped Calcium‐Phosphate Nanocrystals into Giant Porous Beads in Gelatin Hydrosol for Biomedical Applications. Issue 11 (19th July 2013) - Li, Zhicheng; Chen, Xiaoyi; Yang, Yongzhu; Yang, Xianyan; Zhang, Lei; Yang, Guojing; Tang, Ruikang; Gou, Zhongru
Abstract Biomolecule–ion interactions that occur during changes in pH value are a crucial but poorly investigated area that underlies the aggregation of inorganic nanocrystals. Meanwhile, the disorderly growth of calcium phosphate (CaP) nanocrystals is an obstacle that limits its practical applications. Herein, we have demonstrated for the first time that a simple two‐step pH‐adjustment process for a gelatin hydrosol reaction medium can modulate the ordered self‐assembly of trace‐element‐doped CaP nanocrystals into porous beads. Two methods are used to adjust the initial pH value of gelatin hydrosol: One is to firstly adjust the pH value to 3.0 and then to 4.0 with acid/base solutions, whilst the other is to directly adjust the pH value to 4.0 with acid. Spherical CaP porous beads are rapidly produced through the two‐step pH‐adjustment process, whereas the one‐step pathway results in disorderly CaP aggregates. We believe that the introduction of additives for pH adjustment is the dominant factor in disturbing the electrokinetic parameters and for driving the self‐assembly of nanocrystals, whereas the nucleation of CaP nanocrystals prior to assembly is caused by the relaxation/condensation of the polypeptide network, owing to the increase in pH value on the introduction of the basic calcium salt. This method is facile and rapid and these highly bioactive porous beads are particularly promising for use in hard‐tissue repair, tissue engineering, and drug delivery.